2014
DOI: 10.1242/jcs.140871
|View full text |Cite
|
Sign up to set email alerts
|

Glypican-3 binds to frizzled and plays a direct role in the stimulation of canonical Wnt signaling

Abstract: Glypican-3 (GPC3) is a proteoglycan that is bound to the cell surface. It is expressed by most hepatocellular carcinomas (HCCs) but not by normal hepatocytes. GPC3 stimulates HCC growth by promoting canonical Wnt signaling. Because glypicans interact with Wnts, it has been proposed that these proteoglycans stimulate signaling by increasing the amount of Wnt at the cell membrane, thus facilitating the interaction of this growth factor with its signaling receptor, Frizzled. However, in this study, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 63 publications
3
142
0
1
Order By: Relevance
“…In hepatocellular carcinoma cells, this oncofetal antigen binds to Frizzled, thereby promoting WNT signaling, which stimulates growth. 78 Our data suggest that the opposite might be true in preeclampsia. The very low-density lipid receptor (VLDLE) was also in this category.…”
Section: Gsta3mentioning
confidence: 65%
“…In hepatocellular carcinoma cells, this oncofetal antigen binds to Frizzled, thereby promoting WNT signaling, which stimulates growth. 78 Our data suggest that the opposite might be true in preeclampsia. The very low-density lipid receptor (VLDLE) was also in this category.…”
Section: Gsta3mentioning
confidence: 65%
“…CM, conditioned medium. mechanism has been proposed to explain GPC3-induced stimulation of Wnt signaling (27). We have recently shown that GPC3 plays a direct role in the activation of Wnt signaling by binding to both Wnt and its receptor Frizzled (Fz) and by stimulating the formation of signaling complexes (27).…”
Section: Discussionmentioning
confidence: 99%
“…mechanism has been proposed to explain GPC3-induced stimulation of Wnt signaling (27). We have recently shown that GPC3 plays a direct role in the activation of Wnt signaling by binding to both Wnt and its receptor Frizzled (Fz) and by stimulating the formation of signaling complexes (27). Because the convertase-resistant GPC3 is as potent as wild-type GPC3 in the stimulation of Wnt signaling (23), our data suggest that the structural changes generated by the lack of convertase cleavage do not alter GPC3-Wnt and GPC3-Fz binding interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analysis indicated that downregulation of GPC-3 with miRNA significantly (p < 0.01) decreases expression of β-catenin, p-GSK3β, and cyclin D1. β-catenin and GSK3β are known to play an important role in regulating metabolism, transcription, embryonic development, and other processes and to also play a key role in the Wnt/β-catenin-induced phosphorylation of GSK3β, which results in the dissolution of the complex responsible for β-catenin degradation (62,63). A therapeutic intervention targeting GPC-3 is a promising approach for the clinical management of HCC.…”
Section: Studies In Vivomentioning
confidence: 99%